The interaction between academia and industry and its impact on national innovation capacity: The case of Algeria. Issue 5 (October 2021) - Saad, Mohammed; Guermat, Cherif; Boutifour, Zohra
The role of higher education institutions (HEIs) in developing the innovative capacity of societies is well recognised. That role is accomplished through the creation and dissemination of knowledge, the success of which is dependent on the types and extent of interactions that can exist between HEIs and industry. Yet this topic remains insufficiently explored in African countries. This paper investigates the extent of the role of Algerian HEIs in cooperating with industry. The main enablers and inhibitors of such activity are also examined.